The Process of directing an Interactive Educational Videos for Deaf and Intellectually Disabled Children at SLBN Dharma Wanita Kota Bogor - Astutik, Endang Ayu Puji; Suparman (Universitas Telkom, 2025)
Educational videos are familiar to the Indonesian people, especially in the world ofeducation, because educational videos contain certain information or teaching materials that can beused by teachers. The making of educational videos cannot be separated from the role of a directorin the process from start to finish to produce quality audio visual works. Deaf (SLB-B) andIntellectually disabled(SLB-C) students at SLBN Dharma Wanita became the reason for making thisfinal project because they saw that the learning carried out by the school had not used animatedvideos, so the director and team were inspired to make audio-visual works in the form of interactiveeducational videos with the theme